SAT0463 Effect of Eight Years of Denosumab Treatment in Postmenopausal Women with Osteoporosis: Five-Year Results from the Freedom Extension. (10th June 2014) - Roux, C.; Papapoulos, S.; Lippuner, K.; Lin, C.J.; Kendler, D.; Lewiecki, E.M.; Brandi, M.L.; Czerwinski, E.; Franek, E.; Lakatos, P.; Mautalen, C.; Minisola, S.; et al.
Abstract : Background: Denosumab (DMAb) is an approved therapy for the treatment of postmenopausal women with osteoporosis at increased risk for fracture. The effects of DMAb treatment for up to 10 years are being evaluated in the 3-year FREEDOM study and its 7-year extension. Objectives: To report the 5-year results of the FREEDOM extension study, representing up to 8 years of continued DMAb treatment. Methods: During the extension, all women received 60 mg of DMAb every 6 months and daily calcium and vitamin D. In this analysis, women in the long-term group received 8 years of DMAb (3 years in FREEDOM and 5 years in the extension); women in the cross-over group received 5 years of DMAb (3 years of placebo in FREEDOM and 5 years of DMAb in the extension). Results: Of the women who entered the extension, 66% completed the 5th year. With 8 years of DMAb treatment in the long-term group, mean bone mineral density (BMD) continued to increase from FREEDOM baseline for cumulative gains of 18.4% at the lumbar spine (LS) and 8.3% at the total hip (TH) (all p <0.0001). With 5 years of DMAb treatment in the cross-over group, there were mean BMD increases from extension baseline of 13.1% at the LS and 6.2% at the TH (all p <0.0001). Serum C-telopeptide was rapidly and similarly reduced after each DMAb dose, with the characteristic attenuation of effect at the end of the dosing period. Incidence of new vertebral and nonvertebral fracture continued to remain low throughout the extension; during year 8, hip fracture incidence was 0.2% and 0.1% for the long-term and cross-over groups, respectively. Overall incidences of adverse events (AEs) and serious AEs were consistent with data reported previously in the extension study. Conclusions: DMAb treatment for up to 8 years was associated with continued increases in BMD, persistent reduction of bone turnover, and low fracture incidence. The benefit/risk profile for DMAb remains favorable. Disclosure of Interest: C. Roux Grant/research support: Bongrain, Lilly, MSD, Consultant for: Amgen, MSD, Novartis, S. Papapoulos Consultant for: Amgen, Axsome, Gador, GSK, Merck, Speakers bureau: Amgen, Eli Lilly, GSK, Merck, Novartis, K. Lippuner Consultant for: Amgen, Eli Lilly, MSD, Takeda, UCB, C. Lin Shareholder of: Amgen Inc., Employee of: Amgen Inc., D. Kendler Grant/research support: Amgen, Astalis, Eli Lilly, Novartis, Pfizer, Consultant for: Amgen, Eli Lilly, Merck, Pfizer, Warner Chilcott, Speakers bureau: Amgen, Eli Lilly, Pfizer, E. M. Lewiecki Grant/research support: Amgen, Lilly, Merck, Consultant for: Agnovos, Amgen, Lilly, Merck, Radius Health, M. Brandi Grant/research support: Abiogen, Alexion, Amgen, Bruno, Eli Lilly, Farmaceutici, MSD, Servier, Shire, Stroder, Consultant for: Alexion, Servier, Speakers bureau: NPS, E. Czerwinski Grant/research support: Amgen Inc., Merck Serono, Servier, E. Franek Grant/research support: Amgen, Consultant for: Novartis, Speakers bureau: Amgen, MSD, Novartis, Servier, Teva, P. Lakatos Consultant for: Amgen, Lilly, Servier, Speakers bureau: Amgen, Lilly, Merck, Roche, Servier, Teva, C. Mautalen Consultant for: Merck, Servier, S. Minisola Speakers bureau: Abiogen, Amgen, Bruno Farmaceutici, Eli Lilly, Merck Sharp & Dohme, J.-Y. Reginster Grant/research support: Amgen, Boehringer, Bristol Myers Squibb, Chiltern, Danone, Galapagos, GlaxoSmithKline, Lilly, Merck Sharp & Dohme, Novartis, Organon, Pfizer, Roche, Rottapharm, Servier, Teva, Therabel, Theramex, Consultant for: Amgen, Asahi Kasei, GlaxoSmithKline, IBSA-Genevrier, Lilly, Merckle, Negma, Novartis, NPS, Nycomed-Takeda, Roche, Servier, Theramex, UCB, Wyeth, S. Jensen: None declared, N. Daizadeh Shareholder of: Amgen Inc., Employee of: Amgen Inc., A. Wang Shareholder of: Amgen Inc., Employee of: Amgen Inc., M. Gavin Shareholder of: Amgen Inc., Employee of: Amgen Inc., R. Wagman Shareholder of: Amgen Inc., Employee of: Amgen Inc., H. Bone Grant/research support: Amgen, Merck, Novartis, NPS, Consultant for: Amgen, Merck, Novartis, Noven, Sucampo, Tarsa, Speakers bureau: Amgen DOI: 10.1136/annrheumdis-2014-eular.1119